1943
DOI: 10.5962/bhl.title.130457
|View full text |Cite
|
Sign up to set email alerts
|

Tail-length differences in snakes, with notes on sexual dimorphism and the coefficient of divergence [and] A graphic method of showing relationships

Abstract: A negative value of the coefficient means that the females exceed the males. The use of the cp sign throughout this paper indicates that the following figure is the standard, rather than the probable, error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 1 publication
1
33
0
3
Order By: Relevance
“…Embora machos e fêmeas nasçam com o mesmo tamanho, podem apresentar taxas de crescimento e a idade da maturação sexual diferentes, demonstrando dimorfismo sexual em estágios posteriores da vida (Shine, 1990). Estudos sobre dimorfismo sexual realizados com indivíduos de Colubridae e Dipsadidae revelaram maior comprimento rostro-cloacal (CRC) em fêmeas (Fitch, 1981;Shine, 1994;Jordão & bizerra, 1996) e maior comprimento de cauda (CC) em machos (kLauber, 1943;cLark, 1966;king, 1989;SantoS Jr & ribeiro, 2005;). Geralmente as fêmeas apresentam maior comprimento total (CT) que os machos, o que pode estar relacionado com seu sucesso reprodutivo (SemLitSch & gibbonS, 1982;Shine, 1994;zug, 2001).…”
unclassified
See 1 more Smart Citation
“…Embora machos e fêmeas nasçam com o mesmo tamanho, podem apresentar taxas de crescimento e a idade da maturação sexual diferentes, demonstrando dimorfismo sexual em estágios posteriores da vida (Shine, 1990). Estudos sobre dimorfismo sexual realizados com indivíduos de Colubridae e Dipsadidae revelaram maior comprimento rostro-cloacal (CRC) em fêmeas (Fitch, 1981;Shine, 1994;Jordão & bizerra, 1996) e maior comprimento de cauda (CC) em machos (kLauber, 1943;cLark, 1966;king, 1989;SantoS Jr & ribeiro, 2005;). Geralmente as fêmeas apresentam maior comprimento total (CT) que os machos, o que pode estar relacionado com seu sucesso reprodutivo (SemLitSch & gibbonS, 1982;Shine, 1994;zug, 2001).…”
unclassified
“…Diferenças no tamanho da cauda também são comuns, indicando que os machos portam caudas mais longas para acomodar o hemipênis e os músculos retratores (kLauber, 1943;cLark, 1966;king, 1989). Janeiro-cinquini et al (1990) Para evitar a influência do cativeiro, foram analisados os espécimes mortos logo após a captura ou que viveram, no máximo, um mês em cativeiro.…”
unclassified
“…We recently (Barbadillo et al, 1995) proposed a hypothesis, similar to that of Klauber (1943) and Clark (1966), for the sexual dimorphism in tail length in lizards. It identifies the male reproductive organs as a morphological constraint on an important function: the capacity to autotomize the tail.…”
Section: Introductionmentioning
confidence: 94%
“…This hypothesis, termed the 'Morphological Constraint' hypothesis by King (1989), was first formulated by Klauber (1943) and Clark (1966) to explain the longer tails of male snakes. These authors suggested that the presence of the copulatory organs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…E a diferenças no tamanho da cauda também são comuns, indicando que os machos possuem caudas mais longas para acomodar o hemipênis e os músculos retratores (KLAUBER, 1943;CLARK, 1966;KING, 1989 Para análise do padrão de atividade e para verificar possíveis diferenças na frequência de indivíduos nas estações do ano (primavera, verão, outono e inverno)…”
Section: Discussionunclassified